2015
DOI: 10.1039/c5ra08006a
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional studies of hydrogen peroxide adsorption and dissociation on MoO3(100) and H0.33MoO3(100) surfaces

Abstract: Hydrogen peroxide (H2O2) adsorption and dissociation mechanisms on MoO3(100) and H0.33MoO3(100) surfaces were studied by means of density-functional computations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…A further weight loss of ≈0.3% is obtained between 70 and 200 °C which is caused by the release of H + from H x MoO 3 . According to the theoretical calculation, the x in H x MoO 3 is estimated to be 0.3 (Table S1, Supporting Information), indicating that there are ≈2 hydrogen dopants in a single unit cell of H 0.3 MoO 3 ,[15b,20] which is a typical compound of type 1 H x MoO 3 . [19a] X‐ray photoelectron spectroscopy (XPS) is used to reveal the oxidation state reduction of Mo upon H + doping (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…A further weight loss of ≈0.3% is obtained between 70 and 200 °C which is caused by the release of H + from H x MoO 3 . According to the theoretical calculation, the x in H x MoO 3 is estimated to be 0.3 (Table S1, Supporting Information), indicating that there are ≈2 hydrogen dopants in a single unit cell of H 0.3 MoO 3 ,[15b,20] which is a typical compound of type 1 H x MoO 3 . [19a] X‐ray photoelectron spectroscopy (XPS) is used to reveal the oxidation state reduction of Mo upon H + doping (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, LanL2DZ basis set is applicable for the elements such as H, Li-La and Hf-Bi, which gives the best results with the pseudopotential approximation. Hence, LanL2DZ basis set is a suitable basis set to optimize α-MoO 3 with pseudopotential approximation [37][38][39]. The HOMO-LUMO gap and density of states spectrum (DOS) of α-MoO 3 nanostructures are calculated using Gauss Sum 3.0 package [40].…”
Section: Methodsmentioning
confidence: 99%
“…40,41 Significantly, the H x MoO 3 surface behaves with highly reversible redox properties, which means that it has high-performance catalytic activity for chemicals with the appropriate redox potential. 42 Fujishima et al reported the synthesis of visible-light-sensitive reversible photochromic films of MoO 3 , revealing a reversible redox event in the Mo atom by controlling the storage and release of free electrons. Firstly, the α-MoO 3 film produces a strong colour enhancement (deep blue) when irradiated with visible light in the air, displaying a distinct visible absorption peak in the UV-vis NIR spectrum (Fig.…”
Section: Fundamental Propertiesmentioning
confidence: 99%